2014
DOI: 10.1007/s10800-014-0737-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anode orientation and flow channel design on performance of refuelable zinc-air fuel cells

Abstract: The effects of anode orientation (whether an anode is located above or under a cathode) and flow channel design (parallel or serpentine flow channel) on the performance of refuelable zinc-air fuel cells (RZAFC) continuously fed with KOH electrolyte were investigated. The performance test was conducted at different electrolyte flow rates of 2, 4, and 6 ml h -1 . A polarization test of the cell was conducted at the initial stage of operation, followed by a long-term current discharge test in potentiostatic mode.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Zinc-air flow batteries use the same cell structure, in which the circulated anolyte employs the metallic zinc slurry dispersed in alkaline electrolyte. [21][22][23][24][25] During discharge, the zinc metal is oxidized, releasing chemical energy in the form of electricity. The formed Zn 2+ then combines with hydroxide ions in the alkaline media, generating zincate ions (Zn(OH) 4…”
Section: Metal-air Flow Batteriesmentioning
confidence: 99%
“…Zinc-air flow batteries use the same cell structure, in which the circulated anolyte employs the metallic zinc slurry dispersed in alkaline electrolyte. [21][22][23][24][25] During discharge, the zinc metal is oxidized, releasing chemical energy in the form of electricity. The formed Zn 2+ then combines with hydroxide ions in the alkaline media, generating zincate ions (Zn(OH) 4…”
Section: Metal-air Flow Batteriesmentioning
confidence: 99%
“…Ito et al [178] showed that a flow rate over 15 cm s -1 helped to improve the cycle life of a zinc negative electrode even at high charge rates as the velocity of the flow encouraged the growth of the dendrites in the same direction, thus prolonging the time till the system short-circuited. A plate-and-frame filter-press, refuellable Zn-air fuel cell [179] with specially designed anode flow channels in two different orientations and assemblies suggested that both aspects of design were important in controlling electrolyte flux and therefore zinc dendrite formation and H2 evolution. [183], proving more effective when using high frequencies and more diluted solutions.…”
Section: Zn0mentioning
confidence: 99%
“…Its high negative reduction potential and low cost, on account of its abundance, make zinc an attractive material for battery applications. Furthermore, zinc electrodes present advantages in terms of safety when compared, for example, to lithium-or bromine-based technologies [6][7][8]. Therefore, several types of zinc-based battery systems were developed [9], and primary zinc-air batteries are prevalent for certain applications [10].…”
Section: Introductionmentioning
confidence: 99%
“…Negative electrode: Zn + 4OH − ⇔ Zn(OH) 4 2− + 2e − (E 0 = −1.26 V) Unlike conventional configurations, in zinc slurry air flow batteries, the anode is formed by zinc particles suspended in a highly alkaline electrolyte forming a slurry which can flow in and out of the system [8,16]. One of the main advantages of zinc slurry air flow batteries is their higher capacity compared to conventional zinc-air batteries.…”
Section: Introductionmentioning
confidence: 99%